Du temps de travail au temps des marchés - Jens Thoemmes (Temporalités)
Following in Le Goff’s footsteps, inspired by the Middle Ages, we use the metaphor of the eruption of merchants’ time in a world dominated by agricultural activities. We retain two qualities of this sort of time. The first relates to the fundamental role which merchants played in the introduction of a precise measurement of working time. The second quality of merchants’ time relates to risk control and especially to controlling price variability. We find these features today in France: temporalities are being overhauled as we experience the passage from working time to the time of the marketplace. Indeed, consecutive to the Auroux Laws of 1982, variability has become a device in collective bargaining, being used for turning working time into a commodity. We analyzed how in 20 years of collective bargaining, the work of the legislator and the negotiators created a new design for social exchange. Those exchanges bear first of all on the introduction of a “variable standard” for working time which has become widespread and secondly, on the situation of the “job market” at the local and the national level. These two evolutions are related to the variations of the goods and labor markets, that the actors of the negotiation seek to control by implementing logics of prediction and supply.